Recent advances in the synthesis of mesoporous materials and their application to lithium-ion batteries and hybrid supercapacitors - Lim, Eunho; Chun, Jinyoung; Jo, Changshin; Hwang, Jongkook (Korean Journal of Chemical Engineering, 2021)
The ever-growing demand for high performance energy storage systems has fueled the development of advanced electrode materials with light weight, high energy/power densities, and stable cycle life. Mesoporous materials play an important role in achieving these goals because of their unique features such as high surface area, tunable pore size, pore volume, and pore structures, as well as adjustable particle size and morphology. In this review, we summarize the recent progress in the synthesis of mesoporous materials and their applications in lithium-ion batteries (LIBs) and lithium-ion hybrid supercapacitors (Li-HSCs) over the past ten years. The block copolymer guided soft-template route is highlighted as a simple and versatile tool for designing mesoporous materials with controlled nano- and macrostructures without complicated synthetic procedures. The structural/morphological benefits of designed mesoporous materials translate into highly improved electrochemical performance in LIBs and Li-HSCs. Finally, future challenges and perspectives on the development of mesoporous materials in energy storage devices are provided, which will be useful both in academia and in industry.
Keywords: Lithium-ion Batteries; Lithium-ion Hybrid Supercapacitors; Mesoporous Materials; Soft Templating Route